Effects of low‐pressure radio‐frequency cold plasma on the biochemical parameters and fatty acid profile of wheat flours. Issue 2 (16th December 2022) - Gao, Guangbiao; Wu, Jianzhang; Wei, Zheng; Li, Xingjun
Abstract: Background and Objectives: Cold plasma (CP) treatment is a promising way to remove mycotoxins from cereal kernels, although its effects on nutrient contents remain unclear. This study evaluates the biochemical parameters, gelatinization properties, and fatty acid profile of Chinese hard‐white wheat flour treated with low‐pressure radio‐frequency (RF) CP (13.56 MHz, 140 Pa, helium or oxygen, 120 W, 0–180 s, 70 g sample). Findings: 120 W oxygen and helium plasma respectively required 90 and 120 s treatment to remove 50% deoxynivalenol (DON) from hard‐white wheat flour samples with 1.22 μg/g DON. A General Linear Model–Univariate analysis shows that oxygen and helium plasma both significantly increased water absorption rate, conductivity, and contents of reducing sugars, amylose, soluble protein, and saturated fatty acids in wheat flours but decreased the contents of soluble amino acids, total, unsaturated, mono‐unsaturated and poly‐unsaturated fatty acids, and enthalpy of gelatinization, and kept gelatinization peak temperature. At the same treatment time, helium plasma induced a higher water absorption rate, conductivity, and contents of pentosan and sulfhydryl groups in wheat flours than oxygen plasma. Oxygen plasma induced more reductions in mono‐ and poly‐unsaturated fatty acids in wheat flours than helium plasma. Compared with the untreated samples, helium plasma increased the values of water SRC, NaHCO3 SRC, and sucrose SRC, but decreased the lactic acid SRC, suggesting that the flour functional polymers were modified by helium plasma treatment, but oxygen plasma kept these four SRC values and did not significantly alter the functional polymers in wheat flour. Conclusion: The treatment with low‐pressure RF CP can increase hydrophilicity, and unsaturated fatty acid oxidation in wheat flours while kept starch gelatinization, and helium plasma can modify the flour's functional polymers. Significance and Novelty: The suitable helium CP treatment (low‐pressure RF, 120 W, and 90–120 s) is a promising way to reduce the contaminants of wheat flours and improve their functional properties.